Prevalence of Menorrhagia in Young Females (Medical Forum Monthly, 2021)
Objective: To Study the Prevalence of Menorrhagia in young FemalesStudy Design: Retrospective studyPlace and Duration of Study: This study was conducted at the Imran Idris Teaching Hospital Sialkot and Shahina Jamil Teaching Hospital Abbottabad during Jan 2018 to Feb 2020.Materials and Methods: Four Hundred patients of Menorrhagia in young female were included in the study. Fifty percent patients were taken from Imran Idris Teaching Hospital Sialkot and 50% patients were taken from Shahina Jamil Teaching Hospital Abbottabad. The history, examination and investigations were recorded on designed Performa. The written informed consent was taken before recording the data. The permission of Ethical Committee was taken before collecting the data and Get Publishing in Medical Journal. The data was analyzed for results by SPSS version 10.Results: The mean age was 19.98 ± 13, adoleseents/a adult patients (ratio) was 2:1, patients with mucosal bleeding other than mcnorrhagia was 17(21.91%), Patients with mcnorrhagia since menarche (%) was 6 (63.88%), patients having history of treatment for Menorrhagia 49 (66.46%), patients with PBAC score of >100 (%) was 65 (88%), patients with sescrelv Alf101 quAli tv C0)1"4 (%) was 17(7.84%), Mean hemoglobin 102.67:26.4, Mean platelet count (.4109/1) was 2121,88221.013.519, Mean prothrombin time was 12.99:1.26, Mean activated partial thrornboplastin time (5) was 28.88±4.81, Mean thrombin time (s) was 15.97:1.26, Mean fibrinogen (g/dt.) was 3.45±1.02, Mean serum rennin (ng/mL) was 14,88:26,87.The bleeding history and characteristics of the patients with congenital clotting defects was evident.The p value was significant between Patients with bleeding disorders and Patients without bleeding disorders in case of Nose bleeding and Easy bruising p<0.001 and comparison was non-significant in rest of the case.Conclusion: It was concluded from the study that now a days it was common problem that young ladies have complaint of Menorrhagia.